2018
DOI: 10.1007/s00253-018-9238-4
|View full text |Cite
|
Sign up to set email alerts
|

Immune response characterization of mice immunized with Lactobacillus plantarum expressing spike antigen of transmissible gastroenteritis virus

Abstract: The highly infectious porcine transmissible gastroenteritis virus (TGEV), which belongs to the coronaviruses (CoVs), causes diarrhea and high mortality rates in piglets, resulting in severe economic losses in the pork industry worldwide. In this study, we used Lactobacillus plantarum (L. plantarum) to anchor the expression of TGEV antigen (S) to dendritic cells (DCs) via dendritic cell-targeting peptides (DCpep). The results show that S antigen could be detected on the surface of L. plantarum by different dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…Recombinant L. plantarum inhibits TGEV and PEDV infections in the IPEC-J2 cell line by enhancing ISGs (OASL, ISG15, and Mx1) which have strong antiviral effects (199). Recombinant L. plantarum (containing the surface S antigen of TGEV) elicits an immune response characterized by higher numbers of activated DC cells, B + IgA + cells, secretory IgA (sIgA), serum IgG, IFN-γ, and IL4 which help the host to combat TGEV (200). Similar effects were observed by Jiang and colleague who reported that a recombinant L. casei ATCC39392 vaccine modulates the immune response against TGEV infection, induces IL4, mucosal (IgA), and systemic (Ghosh and Higgins) antibodies, and polarized Th2 immune response with enhanced the expression of IL17 against TGEV in a pig model (201).…”
Section: Coronavirusmentioning
confidence: 99%
“…Recombinant L. plantarum inhibits TGEV and PEDV infections in the IPEC-J2 cell line by enhancing ISGs (OASL, ISG15, and Mx1) which have strong antiviral effects (199). Recombinant L. plantarum (containing the surface S antigen of TGEV) elicits an immune response characterized by higher numbers of activated DC cells, B + IgA + cells, secretory IgA (sIgA), serum IgG, IFN-γ, and IL4 which help the host to combat TGEV (200). Similar effects were observed by Jiang and colleague who reported that a recombinant L. casei ATCC39392 vaccine modulates the immune response against TGEV infection, induces IL4, mucosal (IgA), and systemic (Ghosh and Higgins) antibodies, and polarized Th2 immune response with enhanced the expression of IL17 against TGEV in a pig model (201).…”
Section: Coronavirusmentioning
confidence: 99%
“…Among these vectors, one of the probiotic strains, lactic acid bacteria (LAB), has raised a lot of interest due to its beneficial properties for human health [2]. To date, a large number of protective antigens have been previously delivered by LAB strains, mainly including Lactococcus lactic (L. lactic) [3][4][5] and Lactobacillus plantarum (L. plantarum) strains [6,7]. Compared with L. lactic strains, the L. plantarum strains are able to colonize more efficiently in the intestinal tract, which is the first step for efficient antigen production and necessary for subsequent antigen processing in host cells.…”
Section: Introductionmentioning
confidence: 99%
“…Our lab has recently used the anchoring sequence from poly-γ-glutamic acid synthetase A (pgsA), a transmembrane protein from Bacillus subtilis [11][12][13] in order to construct recombinant L. plantarum strains capable in expressing foreign antigens. The resulting strains were efficient in the production of protective antibody responses and partial protection against either influenza virus [14], transmissible gastroenteritis virus [15,16] or porcine epidemic diarrhea virus [17]. Notably, the traditional recombinant L. plantarum vaccines still relies on antibiotic resistance markers such as erythromycin, ampicillin or kanamycin.…”
mentioning
confidence: 99%